Ketidaklengkapan Pengisian Dokumen Clinical Pathway Kanker Paru (Studi Kualitatif di RSUP H.Adam Malik tahun 2021) - Fajrinur, Fajrinur; Handini, Myrnawati Crie; Tarigan, Frida Lina; Harefa, Karnerius; Ginting, Daniel (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2022)
Abstrak Pelaksanaan clinical pathway (CP) pada pasien kanker paru akan menurunkan jumlah hari rawat inap pasien di rumah sakit. Penelitian bertujuan menggali lebih dalam ketidakkelengkapan pengisian dokumen clinical pathway (CP) kanker paru di RSUP H. Adam Malik tahun 2021. Metode penelitian adalah kualitatif dengan pendekatan fenomenologi di RSUP H. Adam Malik pada bulan Maret - September 2021. Informan penelitian diambil secara purposive sampling, sebanyak enam informan dengan kriteria pegawai yang terlibat didalam pembuatan, perencanaan, penyusunan dan pelaksanaan clinical pathway, memiliki masa kerja lebih dari dua tahun, mampu berkomunikasi dengan baik dan bersedia menjadi informan. Informan tersebut terdiri dari Kepala Bidang Pelayanan medik, Kepala Bidang Case Manager, Dokter bagian Paru, Kepala Perawat/perawat pelaksana bagian paru, Rekam Medik dan Tenaga Farmasi. Penelitian menggunakan metode analisis data Colaizzi. Penelitian menemukan empat hal penting dalam ketidaklengkapan pengisian clinical pathway kanker paru yaitu 1) Komunikasi: Sosialisasi clinical pathway kanker paru belum berjalan dengan optimal 2) Sumber daya: Sumber daya yang mengaudit pengisian clinical pathway belum tersedia khusus 3) Disposisi: Kurangnya komitmen dalam pengisian clinical pathway di rumah sakit 4) Struktur birokrasi: Struktur birokrasi yang mendukung pengisian clinical pathway. Kesimpulan penelitian adalah masih ditemukan lembaran clinical pathway tidak diisi secara lengkap. Disarankan untuk menyusun Standar Operasional Prosedur (SOP) khusus untuk pelaksanaan clinical pathway kanker paru untuk meningkatkan komitmen dalam pengisian clinical pathway kanker paru.Kata kunci: clinical pathway, kanker paru, rumah sakit, SOPÂ AbstractImplementation of clinical pathway (CP) in lung cancer patients will reduce the number of days of hospitalization for patients. This study aims to dig deeper into the incompleteness of filling out clinical pathway (CP) documents for lung cancer at H. Adam Malik Hospital in 2021. The research method was qualitative with a phenomenological approach at H. Adam Malik Hospital in March - September 2021. Research informants were taken by purposive sampling. , as many as six informants with the criteria of employees who are involved in the creation, planning, preparation and implementation of clinical pathways, have a working period of more than two years, are able to communicate well and are willing to become informants. The informants consisted of the Head of the Medical Services Division, the Head of the Case Manager Division, the Lung Doctor, the Chief Nurse/nurse implementing the Pulmonary Section, Medical Records and Pharmacy Staff. The study used the Colaizzi data analysis method. The study found four important things in the incomplete filling of lung cancer clinical pathways, namely 1) Communication: Socialization of lung cancer clinical pathways has not run optimally 2) Resources: Resources that audit clinical pathway filling are not specifically available 3) Disposition: Lack of commitment in filling clinical pathways pathways in hospitals 4) Bureaucratic structure: A bureaucratic structure that supports filling out clinical pathways. The conclusion of the study was that clinical pathway sheets were still not filled out completely. It is recommended to develop a special Standard Operating Procedure (SOP) for the implementation of lung cancer clinical pathways to increase commitment in filling lung cancer clinical pathways.Keywords: clinical pathway, lung cancer, hospital, SOP